Sticks and stones: the impact of the definitions of brownfield in policies on socio-economic sustainability - Tang, Yu-Ting; Nathanail, C. Paul (MDPI, 2012)
Many countries encourage brownfield regeneration as a means of sustainable development but define “brownfield” differently. Specifically, the definitions of brownfield in the regeneration policies of countries with higher population densities usually promote recycling land that is previously developed, whether or not there is chemical contamination. Further, the de facto definition of brownfield used by the UK government focuses on previously developed land that is unused or underused. The ANOVA in this study revealed that local authorities in England (n = 296) with higher percentages of derelict and vacant land tended to be more deprived based on the English Indices of Multiple Deprivation, which evaluate deprivation from the aspects of income, employment, health, education, housing, crime, and living environment. However, the percentage of previously developed land in use but with further development potential had no significant effect on the deprivation conditions. The Blair-Brown Government (1997~2010) encouraged more than 60% of new dwellings to be established on the previously developed land in England. The analyses in this study showed that this target, combined with the definition of brownfield in the policy, may have facilitated higher densities of residential development on previously developed land but without addressing the deprivation problems. These observations indicate that a definition of brownfield in regeneration policies should focus on previously developed land that is now vacant or derelict if land recycling is to contribute to sustainable communities.